Black Cities in Brazil: : The Bahia of all saints, orixás, inkices and caboclos - José de Oliveira , Reinaldo (Latitude, 2023)
The interpretation of black cities aims to better understand the reality of black spaces, racial segregation and territory. We assess that the idea of racial segregation is based on categories of social class, gender, ethnicity and race and territory, however, the reality of the Americas, especially Brazilian, must be observed, especially the time-space of colonization, slavery and racism. We used as a theoretical-methodological instrument, first, the statistical data of the IBGE Census of 2010, on the population classified by blacks and whites, and income. Second, for a better design, we dialogue with authors from both fields of ethnic-racial relations and the literature on the city, the urban and the territory. In our considerations, it will be a great challenge for the Americas, Brazil and Bahia, the promotion of public policies for the inscription of anti-racist and democratic cities with equity.